Ответы и объяснения

2011-05-31T10:00:18+00:00

0,8(5-х)-1,2(х+4)=-2,8

0,8*5-0,8х-1,2х-1,2*4=-2,8

-0,8х-1,2*х=-2,8-4+4,8

-2х=-2

х=-2/-2

х=1 

 

2011-05-31T10:17:36+00:00

Спочатко потрібно взяти: 0,8(5-х)-1,2(х+4)=-2,8

                                            0,8*5-0,8х-1,2-1,2*4=-2,8

                                            -0,8х-1,2*х=-2,8-4+4,8

                                            -2х=-2

                                             х=-2:2

                                             х=-1

Відповідь: -1.